1995
DOI: 10.1038/nsb0895-654
|View full text |Cite
|
Sign up to set email alerts
|

The multisubunit active site of fumarase C from Escherichia coli

Abstract: The crystal structure of the tetrameric enzyme, fumarase C from Escherichia coli, has been determined to a resolution of 2.0 A. A tungstate derivative used in the X-ray analysis is a competitive inhibitor and places the active site of fumarase in a region which includes atoms from three of the four subunits. The polypeptide conformation is similar to that of delta-crystallin and is comprised of three domains. The central domain, D2, is a unique five-helix bundle. The association of the D2 domains results in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
169
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(174 citation statements)
references
References 36 publications
3
169
0
2
Order By: Relevance
“…These correspond to region 1 H133 to T150, region 2 G189 to E204, and region 3 G321 to E335 in human FH. 9 These have been shown to be important in formation of the active A-site and B-site and have some overlap with the regions that may represent mutational hotspots (Figure 2). The clustal alignment across seven species showed that, of distinct missense mutations of FH in MCUL, 16 of 26 (60%) were of fully conserved, 5 of 26 (20%) of strongly conserved, 4 of 26 (16%) of weakly conserved, and 1 of 26 (4%) of nonconserved residues (Table 2, Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These correspond to region 1 H133 to T150, region 2 G189 to E204, and region 3 G321 to E335 in human FH. 9 These have been shown to be important in formation of the active A-site and B-site and have some overlap with the regions that may represent mutational hotspots (Figure 2). The clustal alignment across seven species showed that, of distinct missense mutations of FH in MCUL, 16 of 26 (60%) were of fully conserved, 5 of 26 (20%) of strongly conserved, 4 of 26 (16%) of weakly conserved, and 1 of 26 (4%) of nonconserved residues (Table 2, Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structures of the E. coli fumarase C and Saccharomyces cerevisiae fumarase have been elucidated. 9,10 The high degree of homology of these Supported by Cancer Research UK (clinical research fellowship to N.A.A. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both homologs form a stable homotetramer containing four active sites, and every active site is composed of residues from three enzyme subunits. Each dumbbell-shaped subunit within the tetramer contains three domains: an N-terminal domain, a central domain, and a C-terminal domain (8)(9)(10). The N-and C-terminal domains are predominantly α-helical and linked by the central domain that consists of five tightly packed helices.…”
mentioning
confidence: 99%
“…The recent three-dimensional structure of the fumarase C of Escherichia coli has identified a binding site for anions which is generated by side chains from three of the four subunits within the tetramer [2]. These same side chains are found in the three most highly conserved regions [3].…”
Section: Introductionmentioning
confidence: 99%